Super-refraction conditions at Dum Dum Airport (MAUSAM, 1957)
Conditions for super-refraction have been studied at Dum Dum airport (Calcutta) with a 3-cm radar. There appears to exist some correspondence between the occurrence of ground fog and mist on the one hand and the appearance of super-standard echoes on the other